'n Verkenning van interetniese afstand by ge- selekteerde hoërskoolleerlinge in Potchefstroom - J. H. Booyens; N.S. Jansen van Rensburg (Communicare)
The principal goals of the study are to implement an adjusted.ersion of the well known Bogardus scale of social distance and also to orientate senior undergraduates regarding research techniques. The scope of the project is limited and stress is laid on the qualitative aspects of the sample. In discussing the results certain comparisons are made with the work of Lever (1968; 1979) and the most important variable correlated with interethnic attitude is the respondent's school. The results of the study indicate that Afrikaans respondents are the most exclusive group, whilst Coloured respondents are the most inclusive in attitude. In comparing the material with that of Lever, a tendency to narrow their distance regarding other population groups is indicated for the former group Differences between the attitudes of English speaking and Afrikaans speaking respondents indicate the exclusion of a simple relationship between inter-ethnic communication on the one hand and pronounced attitudes on the other hand